Strategi Pengembangan Pelabuhan Perikanan Nusantara Sungailiat Provinsi Kepulauan Bangka Belitung Untuk Menunjang Kegiatan Perikanan Tangkap. - Zasti, Raisyanfa; Rosyid, Abdul; Boesono, Herry (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Sungailiat Fishery Port type B was the center of fishing activities in Bangka Belitung. This was supported by the location of its strategic location that has the potential to own a good fhishery resources.the era of decentralization was entered by indonesia,each district was required to be able to support their own region to optimize the full potential of the area both real and non real sector. Therefore, in the fisheries sector,was founded Sungailiat Fishery Port Type B.The study aims to identification urgency the condition of facilities, to analyzed develovment of optimization facilities, and analyzed appropriate strategies to be applied in the development of PPNS with current condition. The method was used in this study was descriptive sampling and purposive sampling analysis of the utilization rate of facilities and SWOT analysis were used in this study. The result was obtained that the existing facilities at the Sungailiat Fishery Port type B was still good condition and still proper to used, with the cruise line utilization rate 116%, 140% harbor pool, pier 92%,5 0% TPI. From these result could be concluded than the optimization of basic facilities and fully functional facilities have not been utilized optimally. While the result was obtained from the application of SWOT analysis S-O strategy (Strength-Opportunity) which means that the strategy in its application to use force to take advantage of an opportunity.